Implementasi Webview Menggunakan Android Pada Website Cinema Kampus - Nurani M, Muhammad Ikmal; Amirulloh, Alif; Mahdi, Arif (Jejaring Penelitian dan Pengabdian Masyarakat (JPPM), 2025)
In the midst of today's rapid technological developments, everyone can easily access various things, one of which is information. Everyone can access various kinds of information, including information related to a particular film channel or TV program. This information is spread very widely on web browsers, just by searching on the web browser, information related to the film you are looking for can be found. However, this is still considered a hassle for some people. For this reason, a WebView application was created from a cinema website. WebView is a UI widget that helps integrate web applications into the native context of Android applications. It provides a powerful mechanism for two-way interaction between the native-end (Java) and web-end (JavaScript) of Android applications. This application aims to make it easier for people to find information related to films or TV content and improve the user's experience in watching films or content. Just by installing and opening this application on a smartphone, someone can easily find out the film or content they are looking for, without having to bother opening the film website URL link. And from the black box testing results, 100% results were obtained which were in line with what was expected.